Model Sinergisitas Kelembagaan dalam Pengembangan Kewirausahaan UMKM Wilayah Perbatasan dengan Pendekatan One Village One Product (OVOP) - Hendri, Muhammad Irfani; Espa, Vitriyan; Hasanudin, Hasanudin (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2018)
This study aims to describe the potential of micro, small and medium enterprises (MSMEs) in the border region and to design a model of institutional synergy in the entrepreneurship development of MSMEs in the border region with the approach of one village one product. The approach taken in this study is a qualitative approach with the case study research type. For analysis purposes, data can be collected using triangulation data collection methods involving observation, interview and documentation as well as Focus Group Discussion (FGD). Based on the model developed in the MSMEs entrepreneurship development in border areas, there are 3(three) institutions that play a role and can synergize with each other, namely business development institutions; village incubator of superior village products and village-owned enterprises.